2010
DOI: 10.1016/j.apmr.2010.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of History Taking and Physical Examination for Assessing Anterior Cruciate Ligament Lesions of the Knee in Primary Care

Abstract: ACL lesions are seen frequently. Based on history taking (effusion, popping sensation, and/or giving way) and physical examination (ADT), GPs can screen for ACL lesions in primary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(86 citation statements)
references
References 25 publications
2
82
2
Order By: Relevance
“…Compared with physical examination, stress radiographs provide a quantifiable and retrievable record of instability. Physical examination alone has often been reported to be inaccurate, subjective, and poorly reproducible for assessing anterior knee laxity [3,23,49,53]. Clinician experience, a patient's pain, tolerance of the examination, and concurrent ligamentous injuries may skew physical examination interpretation, detracting in certain situations from its clinical use [22,25,27].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with physical examination, stress radiographs provide a quantifiable and retrievable record of instability. Physical examination alone has often been reported to be inaccurate, subjective, and poorly reproducible for assessing anterior knee laxity [3,23,49,53]. Clinician experience, a patient's pain, tolerance of the examination, and concurrent ligamentous injuries may skew physical examination interpretation, detracting in certain situations from its clinical use [22,25,27].…”
Section: Introductionmentioning
confidence: 99%
“…Uninterpretable index test outcomes, such as an equivocal finding were dealt with as a negative index test finding. The authors of one study [19] were contacted and provided additional information.…”
Section: Data Extractionmentioning
confidence: 99%
“…Of the 14 included articles, 10 had a prospective study design [19,23,24,[28][29][30][32][33][34][35], two used a retrospective design [26,27] and for two studies [25,31] the design was unclear (Table 1).…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 In primary care, however, the use of MRI in knee injuries is not yet common practice, but is slowly being introduced. It has previously been shown that patient characteristics, history taking, and physical examination have limited value in diagnosing meniscal and ligament damage; [19][20][21] as MRI is an additional tool in diagnosing such damage, 17,18 it is worthwhile to establish whether or not it has additive prognostic value in primary care.…”
Section: Introductionmentioning
confidence: 99%